2011
DOI: 10.19030/jabr.v16i2.2035
|View full text |Cite
|
Sign up to set email alerts
|

The Importance Of Decision Confidence To Strategy Outcomes

Abstract: <p class="MsoNormal" style="text-align: justify; margin: 0in 0.5in 0pt; mso-pagination: widow-orphan;"><span style="font-family: Batang; font-size: x-small;">Strategic marketing researchers are of the view that formulating high quality strategies is sufficient for achieving high strategy success rates.<span style="mso-spacerun: yes;">&nbsp; </span>This research study investigates the effect of key organizational and managerial variables on the outcome of strategies.<span style="m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…According to McMullen and Shepherd, 'more knowledge can lead to overcoming beliefrelated doubt that would otherwise prevent action' (in Heavey et al, 2009Heavey et al, : 1293. In other words, more information and analyses increase the level of confidence in a decision (Adidam and Bingi, 2000). Therefore, our second hypothesis is as follows:…”
Section: Human Capitalmentioning
confidence: 98%
See 3 more Smart Citations
“…According to McMullen and Shepherd, 'more knowledge can lead to overcoming beliefrelated doubt that would otherwise prevent action' (in Heavey et al, 2009Heavey et al, : 1293. In other words, more information and analyses increase the level of confidence in a decision (Adidam and Bingi, 2000). Therefore, our second hypothesis is as follows:…”
Section: Human Capitalmentioning
confidence: 98%
“…If fulfilled, the requirement of more information and analyses by decision-makers with higher levels of education (Gimeno et al, 1997;Papadakis et al, 1998) ultimately lead to more comprehensive decisions which generate stronger belief and trust and positively affects the amount of resources and time spent during implementation (Adidam and Bingi, 2000). Therefore, we hypothesize that:…”
Section: Level Of Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Previous work has suggested that graphical displays improve confidence in various decision-making tasks. Related studies have used a similar approach for rating confidence (Kamis & Stohr, 2006;Adidam & Bingi, 2000), and previous research has suggested that the use of an interactive visual interface may improve confidence (Sharkey, Acton, & Conboy, 2009). Increased confidence may result in better outcomes from decision-making, for example, increased confidence can result in following through with a financial plan (Lusardi & Mitchell, 2005).…”
Section: Elicited Confidencementioning
confidence: 99%